1983
DOI: 10.1172/jci111016
|View full text |Cite
|
Sign up to set email alerts
|

Urinary calcium excretion in familial hypocalciuric hypercalcemia. Persistence of relative hypocalciuria after induction of hypoparathyroidism

Abstract: A B S T R A C T Familial hypocalciuric hypercalcemia (FHH) is an autosomal dominant trait comprising hypercalcemia, hypophosphatemia, parathyroid hyperplasia, and unusually low renal clearance of calcium. We evaluated the role of parathyroid hormone in the relative hypocalciuria of FHH and characterized the renal transport of calcium in this disorder using three previously hypercalcemic FHH patients with surgical hypoparathyroidism and three controls with surgical hypoparathyroidism. Intravenous infusion of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(85 citation statements)
references
References 31 publications
(40 reference statements)
4
81
0
Order By: Relevance
“…Additional evidence of the role of CASR in regulating Ca 2+ and Mg 2+ transport in CTAL is found in subjects with mutations in the CASR gene. In subjects with FHH due to an inactivating mutation in the CASR there is a PTH-independent increase in tubular Ca 2+ reabsorption (48), while in ADH subjects there is increased urinary calcium excretion (31).…”
Section: Regulation Of Calcium Excretion In Kidneymentioning
confidence: 99%
“…Additional evidence of the role of CASR in regulating Ca 2+ and Mg 2+ transport in CTAL is found in subjects with mutations in the CASR gene. In subjects with FHH due to an inactivating mutation in the CASR there is a PTH-independent increase in tubular Ca 2+ reabsorption (48), while in ADH subjects there is increased urinary calcium excretion (31).…”
Section: Regulation Of Calcium Excretion In Kidneymentioning
confidence: 99%
“…1). Although there is no direct evidence of a calcium receptor effect on phosphate transport, it is found that subjects with benign hypocalciuric hypercalcemia due to insensitivity of the calcium receptor show less phosphaturia than patients with the same degree of hypercalcemia due to primary hyperparathyroidism [11]. It will further support our hypothesis that management of hypercalcemia would improve TRP.…”
Section: Role Of Calcium In Renal Phosphate Handlingmentioning
confidence: 63%
“…The degree of hypercalcemia depends on how severely the variant affects the function of CaSR (6). Similarly, in the renal tubules, calcium reabsorption is increased causing a relatively low renal calcium excretion (7,8,9). Recently, similar phenotypes have been shown to be attributable to mutations in the G protein alpha 11 (Ga11(GNA11)) gene (FHH type 2) and adaptor protein 2 sigma 1 (AP2S1) gene (FHH type 3) with loci placed on chromosomes 19p and 19q respectively (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of FHH, PTX is not only unnecessary but also inappropriate, as it does not cure FHH-associated hypercalcemia (3,9). When FHH is not considered as an alternative diagnosis, failed PTX may lead to a suspicion of persistent PHPT with the risk of subsequent neck explorations, postoperative hypoparathyroidism, and recurrent laryngeal nerve palsy.…”
Section: Introductionmentioning
confidence: 99%